2006
DOI: 10.1063/1.2148408
|View full text |Cite
|
Sign up to set email alerts
|

On the theory of the reaction rate of vibrationally excited CO molecules with OH radicals

Abstract: The dependence of the rate of the reaction CO+ OH→ H+CO 2 on the CO-vibrational excitation is treated here theoretically. Both the Rice-Ramsperger-Kassel-Marcus ͑RRKM͒ rate constant k RRKM and a nonstatistical modification k non ͓W.-C. Chen and R. A. Marcus, J. Chem. Phys. 123, 094307 ͑2005͒.͔ are used in the analysis. The experimentally measured rate constant shows an apparent ͑large error bars͒ decrease with increasing CO-vibrational temperature T v over the range of T v 's studied, 298-1800 K. Both k RRKM ͑… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 41 publications
0
10
1
Order By: Relevance
“…The OH exposure is determined using the rate coefficient of CO + OH ( k OH+CO, 298K = 1.5 × 10 −13 cm 3 molec −1 s −1 ), assuming pseudo-first order kinetics. 36 The OH exposure can be converted to “days of equivalent aging” using typical tropospheric OH concentrations ([OH] = 1.0 × 10 6 molec cm −3 ). 37 O 3 concentrations were monitored downstream of each of the OFRs using an O 3 analyzer (Model 202 and Model 106-L, 2B Technologies).…”
Section: Methodsmentioning
confidence: 99%
“…The OH exposure is determined using the rate coefficient of CO + OH ( k OH+CO, 298K = 1.5 × 10 −13 cm 3 molec −1 s −1 ), assuming pseudo-first order kinetics. 36 The OH exposure can be converted to “days of equivalent aging” using typical tropospheric OH concentrations ([OH] = 1.0 × 10 6 molec cm −3 ). 37 O 3 concentrations were monitored downstream of each of the OFRs using an O 3 analyzer (Model 202 and Model 106-L, 2B Technologies).…”
Section: Methodsmentioning
confidence: 99%
“…More detailed investigations of revealed that HOCO is formed in vibrationally excited state HOCO*. ,, This hot intermediate may further deactivate in one of three channels: stabilization by a third particle M in , redissociation back to the reactants in , and product formation in Several studies ,,,,, focused on the vibrationally excited reactants: OH* and CO*. The rate constant for was shown to decrease ,, when CO* is involved but to increase with OH* involvement.…”
Section: Introductionmentioning
confidence: 99%
“…More detailed investigations of revealed that HOCO is formed in vibrationally excited state HOCO*. ,, This hot intermediate may further deactivate in one of three channels: stabilization by a third particle M in , redissociation back to the reactants in , and product formation in Several studies ,,,,, focused on the vibrationally excited reactants: OH* and CO*. The rate constant for was shown to decrease ,, when CO* is involved but to increase with OH* involvement. Participation of the third particle in results in the rate increase for the overall reaction with increasing pressure. ,,,,,,,, The nature of M is also important: while He diluent was found to be less efficient, H 2 and SF 6 increase reaction rate to a greater extent. At the same time, O 2 /Ar mixture has no effect .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The OH exposure at each lamp intensity was determined by introducing carbon monoxide to the OFR and measuring the drop in CO concentration due to oxidation using a CO analyzer (APMA-370, Horiba Ltd). The OH exposure is determined using the rate coefficient of CO + OH (kOH + CO, 298K = 1.5×10 -13 cm 3 molec -1 s -1 ), assuming pseudo-first order kinetics (Chen and Marcus, 2006). The OH exposure can be converted to "days of equivalent aging" using typical tropospheric OH concentrations ([OH] = 1.0 × 10 6 molec•cm -3 ) (Wolfe et al, 2019).…”
Section: Ofr Operationmentioning
confidence: 99%